Dictation mistakes In Iraqi News - papers - شهلاء عبد الرحمن جابر (College of Education for Women, 2019)
The aim of this research is subjected to discover The Dictation mistakes which occur widely in the Arabic Language written by Iraqi - News papers. The research classified These Mistakes in Three groups as Follows: 1. The first group dealing with distinguishing between the Arabic - letter ) ا ( When Written or ) أ ( at The beginning The word and as ) ئ ( which differ in meaning from each other . 2. The second group dealing with the writing of The Arabic ) ٙ( and as ) ٛ( at the end of The word which differ in meaning from each other. 3. The Third group dealing with distinguishing in written The Arabic letter as ) ض( or as ) )ظ which differ in meaning From each other. 4. The fourth group dealing with The writing The one Arabic - letter sometime as ) ٕ ( and other time as ) ح( which differ each other .